PENGARUH TIKTOK LIVE TERHADAP PENINGKATAN PENJUALAN PADA AKUN TIKTOK @GROSIRANJAMSTORE - Sitti Hadija (CV Edujavare Publishing, 2024)
This thesis aims to analyze the influence of live broadcasting sessions on the TikTok platform on sales growth for the TikTok account @GrosiranJamStore. The research method employed is descriptive qualitative research using the Stimulus Organism Response (SOR) theory approach. Data were obtained through observations of interactions between the account owner and TikTok users during live broadcasting sessions, as well as an analysis of sales growth before, during, and after the live broadcasting sessions. The findings of this research are expected to provide a better understanding of the potential use of TikTok Live as an effective marketing tool to increase sales on e-commerce platforms. Additionally, this study may offer new insights into applying the SOR theory in the context of social media influence on consumer behavio.